Electrostatic mechanism of strong enhancement of light emitted by semiconductor quantum wells - Llopis, A. (2017)
Currently, it is understood that the carrier recombination rate in semiconductors can be modified by metals due to pure electrodynamic interactions through surface plasmons. We propose here an electrostatic mechanism for carrier-metallic nanoparticle interaction comparable in effect to plasmonic interactions. Arising from Coulomb attraction of electrons and holes to their images in metal, this mechanism produces large carrier concentrations near metallic nanoparticles. Increased concentration results in increased quantum efficiency and enhances the rate of e-h recombination. This manifests as emission enhancement in InGaN quantum wells radiating in the near-UV region. The proposed fundamental mechanism provides a new perspective for improving the efficiency of broadband light emitters.